Intelligent video event analysis and understanding - Zhang, Jianguo (Studies in computational intelligence, 2011)
Presenting state-of-the-art research advances of video event understanding technologies, this volume is a rich resource for future research and successful practice. The text covers visual surveillance, human-computer interaction, and video search and indexing etc.